Infographic. International Olympic Committee (IOC) consensus statement and clinical decision-making guide on acute respiratory illness in athletes - Mackie, M. R.; Schwellnus, M.; Thornton, J. S. (British Journal of Sports Medicine, 2024)
These infographics seek to summarise the International Olympic Committee (IOC) consensus statements on acute respiratory illness in athletes.1 2 Figure 1 provides a brief overview from the IOC consensus statement Part 1: acute respiratory infections,1 and Part 2: non-infective acute respiratory illness.2 Figure 2 provides the Sport & Exercise Medicine (SEM) clinician with an algorithm to guide clinical decision-making for athletes with an acute respiratory infection. The algorithm follows a four-step process, which examines infection severity, athlete health risk, activity risk and risk tolerance.1 Figure 3 provides both postexercise checklists for athlete/support staff and clinician to guide …